Steering Controller Design for Smart Autonomous Surface Vessel Based on CSF L2 Gain Robust Strategy - Guan, Wei; Cao, Weinan; Sun, Jinghai; Su, Zuojing (IEEE access, 2019)
During the mission at sea, the yaw motion of the smart autonomous surface vessel (SASV) is always subject to the external disturbances. These issues make the design of a robust controller for steering autopilot system a quite challenging task. This paper focuses on the utilization of closed-loop shaping filter (CSF) to improve the SASV steering L2 gain robust control scheme. First, the mathematical model of the SASV is proposed and the parameters of the SASV model are obtained by the recursive least squares method (RLSM) based on the SASV turning test. Then the CSF L2 gain nonlinear robust controller design for SASV steering autopilot is described, and the stability and robustness of the proposed controller are proved based on the Lyapunov synthesis. Finally, the strong robustness and superior control performance are demonstrated through the practical SASV experiments. At the same time, the concise controller structure and definite physical meaning of SASV controller parameters are also concluded.